3‐D basin‐scale reconstruction of natural gas hydrate system of the Green Canyon, Gulf of Mexico. (18th May 2017) - Burwicz, Ewa; Reichel, Thomas; Wallmann, Klaus; Rottke, Wolf; Haeckel, Matthias; Hensen, Christian
Abstract: Our study presents a basin‐scale 3‐D modeling solution, quantifying and exploring gas hydrate accumulations in the marine environment around the Green Canyon (GC955) area, Gulf of Mexico. It is the first modeling study that considers the full complexity of gas hydrate formation in a natural geological system. Overall, it comprises a comprehensive basin reconstruction, accounting for depositional and transient thermal history of the basin, source rock maturation, petroleum components generation, expulsion and migration, salt tectonics, and associated multistage fault development. The resulting 3‐D gas hydrate distribution in the Green Canyon area is consistent with independent borehole observations. An important mechanism identified in this study and leading to high gas hydrate saturation (>80 vol %) at the base of the gas hydrate stability zone (GHSZ) is the recycling of gas hydrate and free gas enhanced by high Neogene sedimentation rates in the region. Our model predicts the rapid development of secondary intrasalt minibasins situated on top of the allochthonous salt deposits which leads to significant sediment subsidence and an ensuing dislocation of the lower GHSZ boundary. Consequently, large amounts of gas hydrates located in the deepest parts of the basin dissociate and the released free methane gas migrates upward to recharge the GHSZ. In total, we have predicted the gas hydrate budget for the Green Canyon area that amounts to ∼3256 Mt of gas hydrate, which is equivalent to ∼340 Mt of carbon (∼7 × 10 11 m 3 of CH4 at STP conditions), and consists mostly of biogenic hydrates. Plain Language Summary: Gas hydrates are ice‐like crystalline deposits containing water and gas molecules. Gas hydrates are stable at low temperature and high pressure subseafloor environments. Due to their chemical composition, gas hydrates are proposed to be an important alternative source of energy. Our numerical modeling study performed on the Green Canyon site in the northern Gulf of Mexico shows that about 340 Mt of carbon can be potentially stored at this location which confirms its high economic potential. Key Points: Complex regional geology (i.e., salt tectonics and faulting) resolved with 3‐D numerical modeling Methane gas recycling process identified at the base of the gas hydrate stability zone Total amount of gas hydrate predicted in the model domain (∼450 km 2 ) equals ∼340 Mt of carbon